2016
DOI: 10.1063/1.4944073
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic alignment in the recombination stage in d-HDDR process of Nd-Fe-B-Ga-Nb powders

Abstract: Nd-Fe-B-Ga-Nb magnetic powder was subjected to the dynamic hydrogen disproportionation desorption recombination treatment. For samples disproportionated at both 30 and 100 kPa of hydrogen pressure, the changes in the microstructure and grain orientation during recombination process were investigated. It was observed that even during the recombination process, the orientation relationship was maintained between α-Fe and NdH2+x grains formed after the disproportionation treatment at 30 kPa of hydrogen pressure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Temp. Ramp Rate [11] H 2 % in Supply Gas * [10][11][12][13][14][15][16][17][18] Dwell Temp. [19][20][21][22][23][24] Total Pressure * [25] Dwell Time [10,21,24,26,27] Gas Introduction Temp.…”
Section: Hd *mentioning
confidence: 99%
See 1 more Smart Citation
“…Temp. Ramp Rate [11] H 2 % in Supply Gas * [10][11][12][13][14][15][16][17][18] Dwell Temp. [19][20][21][22][23][24] Total Pressure * [25] Dwell Time [10,21,24,26,27] Gas Introduction Temp.…”
Section: Hd *mentioning
confidence: 99%
“…Ramp Rate [none] 1st Vacuum Pressure [28,29] Dwell Temp. [19,22,23,[30][31][32] 2nd Vacuum Pressure [33] Dwell Time [16,26,28,29,31,32,34,35] -…”
Section: Hd *mentioning
confidence: 99%
“…Although various models of the induction mechanism of magnetic anisotropy during HDDR treatment have been proposed, [36][37][38] the prevailing theory is as follows. [39][40][41][42] First, it was observed that disproportionation treatment under conditions near the P H2 -T curve led to orientation relationships of [110]¡-Fe // [110]NdH 2+x and (¹110)¡-Fe // (¹220)NdH 2+x between the ¡-Fe and NdH 2+x grains. In addition, the recombined Nd 2 Fe 14 B grains were clearly aligned with orientation relationships of (001)Nd 2 Fe 14 B // (110)¡-Fe and (001)Nd 2 Fe 14 B // (110)NdH 2+x .…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] The other one is Magfine Nd-Fe-B anisotropic magnetic powder prepared using a Hydrogenation-Disproportionation-Desorption-Recombination (HDDR) route. [16,17] Each particle of the anisotropic magnetic powder of MQA-or Magfine-Nd-Fe-B contains several millions of Nd2Fe14B grains. However, the distribution of magnetic easy axes of Nd2Fe14B grains (or [001] crystallographic orientation) is not completely aligned along a single direction in each particle [15,18].…”
Section: Introductionmentioning
confidence: 99%
“…One is Magnequench anisotropic (MQA) Nd-Fe-B anisotropic magnetic powder, produced by hot-deformation (or die-upsetting) of powders derived from melt-spun Nd-Fe-B ribbons [14,15]. The other is Magfine Nd-Fe-B anisotropic magnetic powder, prepared using a hydrogenation-disproportionation-desorptionrecombination (HDDR) method [16,17]. Each particle of the anisotropic magnetic powder of MQA or Magfine Nd-Fe-B contains several million Nd 2 Fe 14 B grains.…”
Section: Introductionmentioning
confidence: 99%